Letter from Carl D. Duncan to Patricia Whiting, July 30, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Carl D. Duncan wrote this letter to Patricia while traveling. Ducan presents a poem in the letter inspired from a picture on a postcard.